Improving Usability of a Mechatronic Drum Robot - U, Jamie (Wellington Faculty of Engineering Symposium, 2023)
This paper details the development of a graphical user interface for DrumBot to improve ease of use. DrumBot is a mechatronic robotic system capable of playing complex MIDI compositions on arbitrary drum kit setups. To prepare DrumBot for a performance, the user must first run the accompanying command line or graphical application and follow through a setup and configuration process. But when this project inherited DrumBot, several significant usability issues were brought to light after testing the graphical user interface. This included requiring text input where one would expect a button or selection input, unexpected hangs in the software, and users possessing little fidelity over certain configuration settings, which made the configuration process confusing and tedious. It was particularly difficult to navigate the setup process for the first time if one was unfamiliar with the inner workings of the system. This project addressed these issues by producing a new GUI application that is more intuitive than the previous. Development involved designing a new user interface, refining the process of configuring the various DrumBot settings, facilitating communications between the host computer and DrumBot, and navigating the challenges of designing an application that safely interfaces with an embedded system. This new application was designed to better guide the user to navigate the DrumBot setup process, and gives the user greater control over configuration, making DrumBot more usable overall.